Os ciclos econômicos e a indústria: uma abordagem recente para a economia brasileira - Bombonati, Rafael Donisete (2016)
The analysis of the theory of business cycles in its global scope had great prominence in the economic science during the second half of the nineteenth century to the middle of the 1929 US crisis. The resumption of this research agenda would only years later, already in the 1970s with the publication of works that allied with the analysis of these fluctuations with the use of econometric tools support. Domestically, the literature devoted to analysis of the Brazilian cycles also have some division within the referred economic thought, with a predominance of authors who used these analyzes in the period before the 1980s, later became effective more related analyzes theories of the economic growth. Already the main elements highlighted in this literature as responsible for the fluctuations observed in the country pointed to the economic development plans, the impact of external shocks and as a result of the stabilization plans. In this sense and taking into account a crisis scenario already in 2015, the domestic industry was eventually raised to alternative to reversing the depressive process observed, even with since the 1980s, a process of disintegration from the debt crisis. Thus the purpose of this study focuses precisely to assess how the industry's behavior, specifically the industrial cycle, impacts the business cycle contraction considering a scenario of industrial activity, classified by many authors as a negative deindustrialization. Thus it structured the argument from an analysis of cycles in its general conceptions and according to some classic authors, later moving to the analysis of Brazilian cycles. Also presented the history of the domestic industry over time as well as its importance from the stylized facts according to the consulted theories. We also used econometric models for this importance could be measured. The results indicate that the industry is losing its ability to influence the national product over time, mainly from the 1980s, which does not mean, however, that it should not be encouraged, since there seems to be some consensus in the literature on its ability to promote growth and economic development through structural change and technological progress. The question that arises, therefore, is which sectors within the industry should be encouraged